Do cyberattacks and religiosity impact customers’ loyalty? Study on Bank Syariah Indonesia - Koeswandana, Noorfaiz Athallah; Yulfiatmi , Mayang Yorindrafitri (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study aimed to investigate the impact of cyberattacks on customer loyalty and satisfaction in the context of Islamic banking, particularly focusing on recent cyberattacks on Bank Syariah Indonesia (BSI).Methodology – Respondents were chosen using purposive sampling and analyzed using Partial Least Square - Structural Equation Modelling (PLS-SEM). 244 respondents participated in this study and were analyzed using SmartPLS 3.2.9 Software.Findings – The results showed that perceived vulnerability and perceived risk negatively influence customer satisfaction, while religiosity positively influences customer satisfaction. Religiosity also has a positive, direct effect on customer loyalty. Surprisingly, perceived severity did not show any significant influence on customer satisfaction after the cyberattacks.Implications – This study can be used by every bank in Indonesia to increase customer loyalty by minimizing the risk that customers might experience, especially in cybersecurity issues.Originality – This study contributes to the literature on customer loyalty after cyberattacks. This study incorporates the religiosity variable in combination with Protection Motivation Theory. Religiosity is expected to have a positive influence on both loyalty and satisfaction, as the research object is Bank Syariah, Indonesia, which offers Islamic financial products. Most customers choose Islamic banks because of the alignment of financial products with Islamic principles (Wijaya et al., 2020).